2013
DOI: 10.1016/s0140-6736(13)60177-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of MVA85A, a new tuberculosis vaccine, in infants previously vaccinated with BCG: a randomised, placebo-controlled phase 2b trial

Abstract: SummaryBackgroundBCG vaccination provides incomplete protection against tuberculosis in infants. A new vaccine, modified Vaccinia Ankara virus expressing antigen 85A (MVA85A), was designed to enhance the protective efficacy of BCG. We aimed to assess safety, immunogenicity, and efficacy of MVA85A against tuberculosis and Mycobacterium tuberculosis infection in infants.MethodsIn our double-blind, randomised, placebo-controlled phase 2b trial, we enrolled healthy infants (aged 4–6 months) without HIV infection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
911
5
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 918 publications
(948 citation statements)
references
References 28 publications
23
911
5
9
Order By: Relevance
“…The vaccine was well tolerated and immunogenic, but it was poorly protective against TB infection [22]. Authors suggested that the immunologic response induced by the vaccine could not be related to protective effect against TB infection.…”
Section: Resultsmentioning
confidence: 99%
“…The vaccine was well tolerated and immunogenic, but it was poorly protective against TB infection [22]. Authors suggested that the immunologic response induced by the vaccine could not be related to protective effect against TB infection.…”
Section: Resultsmentioning
confidence: 99%
“…This antigen was selected on the basis of conservation among all mycobacterial species as a vaccine candidate, MVA85A (40). MVA85A recently was evaluated in phase II trials in which it was used to boost bCG vaccinees, but it failed to protect against MTB infection (41). Interestingly, response to this antigen has not yet been shown to be dominant following bCG vaccination in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Immunological responses considered critical for long-term mycobacterial control have focused on conventional T cell responses directed at peptide antigens presented by major histocompatibility complex (MHC) I and II, ultimately leading to secretion of anti-microbial cytokines, including TNF-α and IFN-γ (3,4). A number of subunit vaccines based on immunogenic peptides have been developed, some of which have been evaluated in clinical trials, but results to date have not been encouraging (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%